Kendali Mutu (Quality Control) Pada Computed Radiology (CR) - Rini Hatma Rusli; Bambang Ariyanto; Maritje S. J Malisngorar; Ira Sandi Tunny (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Computed Radiography (CR) is a radiographic system that can convert analog signals into digital signals so that they are easily processed by image processing , to deal with the inconsistency of image quality from errors in lighting . One of the problems in CR is that the radiograph results are less than the maximum and can inhibit or reduce the ability to diagnose. This study aims to determine how the quality control of CR. This type of research is carried out in literature ( library study) that is by reading literature that has to do with the research conducted, as well as from other sources relating to Quality Control Computed Radiography (CR) and draw conclusions based on existing data. Based on the available literature, it can be concluded that the quality control on Computed Radiography (CR) is different but it does not reduce in terms of improving the quality of Computed Radiography (CR) in producing quality radiographs and can establish diagnoses.